KAJIAN FILSAFAT HUKUM TERHADAP HAKEKAT RASA KEADILAN MASYARAKAT ADAT BALI DALAM SISTEM HUKUM NASIONAL - Holys Abdiel Lumira; I Nyoman Bagiastra (Jurnal Komunikasi Hukum, 2024)
Legal philosophy according to Hans Kelsen is study of law as system of norms that regulate human behavior in society that is abstract and generally applicable. Legal philosophy is also a scientific discipline that seeks knowledge about true and fair law, which in this research aims to conduct a legal philosophy study essence of Balinese justice indigenous people in the national legal system. The problem lies in the disharmony between justice according to national law and customary law, this studies are needed that can create legal harmonization between Balinese Customary Law and National Law or Balinese Customary Law and Customary Law in other regions. The creation of legal harmonization is sought to achieve a sense of justice for each indigenous community. This certainly requires further research that existing norms can keep up with developments in modern society. Apart from that, it is necessary to study what are the parameters of the Balinese Customary Law community it can be used as a definite or proportional measure in order to provide Legal Certainty if Customary Law is to become part of National Law.